Pengaruh Good Corporate Governance, Leverage, Dan Firm Size Terhadap Pengungkapan Risiko (International Forum of Researchers and Lecturers, 2024)
This research aims to determine the effect of good corporate governance, leverage, and firm size on risk disclosure in banking companies listed on the Indonesia Stock Exchange in 2019-2021. The population in this research are banking companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique used purposive sampling technique and obtained 33 companies with a research period of 3 years. The analytical method used in this study is multiple linear analysis using SPSS software version 25.0. Based on the results of the research conducted, it was found that, (1) the Independent Board of Commissioners has no effect on risk disclosure, (2) the Audit Committee has a positive effect on risk disclosure, (3) Leverage has a positive effect on risk disclosure, (4) Firm Size has a positive effect on risk disclosure.